MEKANISME PERALIHAN HAK GUNA BANGUNAN MENJADI HAK MILIK BERDASARKAN PERATURAN MENTERI NEGARA AGRARIA/KEPALA BADAN PERTANAHAN NASIONAL NOMOR 6 TAHUN 1998 DI KECAMATAN MARO SEBO KABUPATEN MUARO JAMBI - Claresa, Yolanda; Fitria, Fitria (Fakultas Hukum Universitas Jambi, 2022)
This study aims to determine and analyze the Mechanism of Transfer of Building Use Rights into Ownership Rights at the Land Agency Office of Muaro Jambi Regency and the factors that hinder the implementation of the transfer of these rights. This study uses the Juridical Empirical research method. The result of the research show that the transfer of building use rights to ownership rights can be seen in the Decree of the State Minister of Agrarian Affairs/Head of the National Land Agency Number 9 of 1997 concerning the Granting of Land Ownership Rights for Simple Houses and Very Simple Houses, the community or homeowners with the status of Building Use Rights can improve the status of their land rights into Ownership Rights through the transfer of land rights in order to obtain guaranteed protection and legal certainty. the aspects that become obstacles in the implementation of the transfer of land rights from building use rights to property rights, namely in making the transfer of land rights, the community often does not complete the file requirements and the community lacks understanding of the procedures or procedures for the transfer of land rights from building use rights become property rights. In addition, the competent authority, namely the Land Agency Office, has not yet fully implemented the transfer of land rights properly. This research is expected to be input for the Government, in this case the National Land Agency to improve performance in public services, disseminate information to the public about the importance of transferring land rights and improve the implementation of land rights transfers that have not been optimal.